The Effect of Health Education About Personal Hygiene in Adolescents on the Prevention of Scabies Disease in Boarding School in Sungai Terap - Ramadhini, Agvira Destri; Nurlinawati, Nurlinawati; Mulyani, Sri (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2023)
Background: Scabies or scabies is an infectious skin disease caused by investment and sensitization of the parasite Sarcoptes Scabiei of the Hominis variety. The World Health Organization (WHO) states that scabies is a very neglected skin disease. It is estimated that 200 million people worldwide suffer from scabies at any one time. The Muara Kumpeh Inpatient UPTD Health Center, located in Muaro Jambi Regency, has the highest incidence of scabies, recorded throughout 2022 there were 112 cases. Based on these data, scabies is experienced by many students or students, one of whom is a student at the Jauharul Falah Islamic Boarding School. This study aims to determine the effect of health education about personal hygiene in adolescents on the prevention of scabies at the Jauharul Falah Islamic Boarding School, Sungai Terap. Methods: This study used a quantitative method with pre-experimental designs with the